LAND USE AND CLIMATOLOGICAL DATA TRENDS IN THE ARC OF AMAZON DEFORESTATION - Ribeiro, Julia; Bourscheidt, Vandoir (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The Amazon Deforestation Arc has been undergoing intense forest removal since the 1970s, resulting in impacts linked not only to the loss of essential environmental services for the maintenance of ecosystems, but also to climatic aspects. In this sense, this work seeks to evaluate the changes in land use in the region and relate them to temperature and precipitation trends (also in terms of consecutive dry and wet days) found through the modified Mann-Kendall test. The research used land use information for the period between 1985 and 2020, provided by the MapBiomas platform and climatological data provided by INMET, whose period varied according to the availability of data from each station. An increase in pastures, urban areas and soybeans was identified, and a decrease in forest and savanna formations. Through the Mann-Kendall test, trends of temperature increase were generally found in the different scales analyzed. For precipitation, no clear trend pattern was identified, although many stations show a reduction in rain over the years. The association between precipitation and temperature trends with different land uses graphically showed that the greatest trends are usually associated with greater changes in use. It is concluded, therefore, that intense changes in land use can influence temperature and precipitation, which can generate future impacts on the local hydrological cycle and affect different sectors of society, reinforcing the importance of actions in favor of forest conservation.